A world map of knowledge in the making: Wikipedia's inter-language linkage as a dependency explorer of global knowledge accumulation - Petzold, T.; Liao, H.; Hartley, John; Potts, J. (The MIT Press, 2012)
Analysis of Wikipedia's inter-language links provides insight into a new mechanism of knowledge sharing and linking worldwide.